Interactions between Host and Oral Commensal Microorganisms are Key Events in Health and Disease Status - Mahmoud Rouabhia (Canadian Journal of Infectious Diseases)
The oral cavity has sometimes been described as a mirror that reflects a person's health. Systemic diseases such as diabetes or vitamin deficiency may be seen as alterations in the oral mucosa. A variety of external factors cause changes in the oral mucosa, thus altering mucosal structure and function, and promoting oral pathologies (most frequently bacterial, fungal and viral infections). Little is known, however, about immune surveillance mechanisms that involve the oral mucosa.